Capital controls and exchange rate expectations in emerging markets - Gustavo Abarca; Claudia Ramírez; José Gonzalo Rangel (Banco de México, 2012)
This article examines changes in the exchange rate expectations associated with capital controls and banking regulations in a group of emerging countries that implemented these measures to control the adverse effects of sudden capital flows on their currencies. The evidence suggests that for most countries the effects of this type of policies are limited. Moreover, in some cases they appear to have an opposite effect from the one intended. In particular, for some currencies our results suggest there were changes in the extremes of their exchange rate distributions, which make their tails heavier and signal that the market allocates a greater probability to extreme movements. In the same way, evidence is found that this type of measures increases the levels of currency risk premium.
Keywords: C14; E44; E58; F31; G15; 330; capital controls; banking regulation; exchange rate expectations; emerging economies; generalized extreme value; Kapitalverkehrskontrolle; Bankenregulierung; Wechselkurs; Schwellenländer